The Effect of Population Behavior on New Renewable Energy in Primary Energy Mix for 2025 National Target: Sumedang Regency Review, West Java - Handoko Handoko; Adianto Adianto; Siow Chee Loon (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
The results of the Study of the Agency for the Assessment and Application of Technology in 2018 estimated the primary energy mix target of renewable energy at 23 (twenty three) percent by 2025 will not be reached. It is estimated that only reach 12.9 (twelve point nine) percent. The use of renewable energy, especially biomass and biogas by the population independently has not been included in the calculation of meeting the energy mix target by the government. Even though the potential of primary energy of bio energy in Indonesia is 32,653.8 MW. This study examines the behavior of the population towards the use of renewable energy, especially biomass and biogas in meeting their needs for cooking and business. The face-to-face research was carried out on 85 (eighty-five) respondents and online as many as 16 (sixteen) respondents in 17 (seventeen) villages in 7 (seven) districts in Sumedang Regency. The study was also conducted on 574 (five hundred seventy four) respondents both online and face to face in 366 (three hundred sixty six) villages in 240 (two hundred forty) districts in 91 (ninety one) districts / cities in 22 (twenty two) provinces. From the results of research and analysis of characteristics, descriptive analysis, logistic analysis and calculations; shows that: (a) trends in 2025, Sumedang residents choose to use biogas fuel, (b) trends in 2025, Indonesians choose to use solid fuels, (c) minimum contribution or potential contribution of Indonesian population to achieving energy mix targets primary New and Renewable Energy of 3.80 (three point eight) percent in 2018 and increased to 8.16 (eight point sixteen) percent in 2025 or about 35 (thirty five) percent of the target of the New and Renewable Energy mix. Thus, this research needs to be followed up and encourage the government through the National Energy Council to conduct more comprehensive research in all regions in Indonesia.